The Hadacol Boogie - Burke, James Lee, 1936- (Burke, James Lee, 1936- Dave Robicheaux novel., 2026)
"Dave Robicheaux, James Lee Burke's iconic detective, returns to investigate the death of an unidentified woman, pulling him into a vortex of corruption and violence in the Louisiana bayou. When a cloaked, disfigured man leaves a dead woman in a garbage bag on Dave Robicheaux's property, he knows his world and family are about to change. With Valerie Benoit, a detective new to the Iberia Parish Sheriff's Department who is grappling with sexist and racist harassment from their colleagues, and the volatile but fiercely loyal Clete Purcel, Dave embarks on an investigation that brings him into the most dangerous moments of his career, including the potential death of Valerie and his daughter Alafair. Dave encounters a local handyman who leaves cryptic notes and warns of the ghosts who roam the shores of the bayou and is targeted by a vicious New Orleans button man and gangsters from the north. Through brilliant prose and a quintessential cast of characters, James Lee Burke weaves a portrait of a gritty, violent Louisiana at the turn of the twentieth century. Visceral, atmospheric, and wholly original, The Hadacol Boogie brings to life Dave Robicheaux's fierce determination to confront evil both past and present"-- Provided by publisher.